HUBUNGAN PELETAKAN KAMERA (ANGLE) DALAM IKLAN BERBENTUK VIDEO - Halim, Bobby; Yulius, Yosef (Jurnal Seni, Desain dan Budaya)
AbstractIn an advertisement sometimes there is a meaning that is presented not straightforward. Every TVC that uses real human talent cannot be separated from the camera's perspective. THE IMPORTANCE OF CAMERA VIEWS ON VIDEO MEDIA ADVERTISING examines the relationship of camera placement (angle) in influencing the message conveyed by a TVC and how cinematography is used as visual rhetoric. The study was conducted qualitatively with a semiotic film analysis approach. Data THE IMPORTANCE OF CAMERA VIEWS ON VIDEO MEDIA ADS is grouped into 4 structures, namely Visual Structure, Verbal Structure (Language, Character, Settings, Time), Narrative Structure and Audio Structure. Diachronic analysis using signifier (sign) and signified (sign) views. Some types of angles are Extreme Long Shot (ELS), Very Long Shot (VLS), Long Shot (LS), Medium Long Shot (MLS), Medium Shot (MS), Medium Close Up (MCU), Close Up (CU), Big Close Up (BCU), Low Angle Shot, Eye Level Shot. The selection of the selected images to be analyzed is carried out on the following basis: (1) Selecting an image according to the type of camera angle. (2) Sort images according to the type of camera angle. (3) Analyze each film and the impression built from each camera's perspective. (4) Comparing the impressions of the two analyzes. (5) Explain the reasons for the different impressions that arise, when the viewpoint of the camera is the same but the impression obtained is different. The camera angle is important in creating certain impressions, for example the impression of horror.Keywords : advertisement, semiotics, film, cinematographyAbstrakDalam sebuah iklan terkadang terdapat makna yang disajikan tidak lugas. Setiap TVC yang menggunakan talent manusia asli, tidak terlepas dari sudut pandang kamera. PENTINGNYA SUDUT PANDANG KAMERA PADA IKLAN MEDIA VIDEO menelaah hubungan peletakan kamera (angle) dalam mempengaruhi pesan yang disampaikan oleh sebuah TVC dan bagaimana sinematografi digunakan sebagai retorika visual. Kajian dilakukan secara kualitatif dengan pendekatan analisis semiotika film. Data PENTINGNYA SUDUT PANDANG KAMERA PADA IKLAN MEDIA VIDEO dikelompokan menjadi 4 struktur, yaitu Struktur Visual, Struktur Verbal ( Bahasa, Karakter, Setting, Waktu), Struktur Naratif dan Struktur Audio. Dianalisis secara diakronik dengan menggunakan pandangan signifier (penanda) dan signified (petanda). Beberapa jenis angle yaitu Extreme Long Shot (ELS), Very Long Shot (VLS), Long Shot (LS), Medium Long Shot (MLS), Medium Shot (MS), Medium Close Up (MCU), Close Up (CU), Big Close Up (BCU), Low Angle Shot, Eye Level Shot. Pemilihan gambar-gambar yang dipilih untuk dianalisa, dilakukan dengan dasar berikut: (1) Memilih gambar yang sesuai jenis sudut pandang kamera. (2) Mengurutkan gambar berdasarkan jenis sudut pandang kamera. (3) Menganalisis masing-masing film dan kesan yang dibangun dari masing-masing sudut pandang kamera. (4) Membandingkan kesan dari kedua analisis. (5) Menjelaskan sebab-sebab perbedaan kesan yang timbul, bila sudut pandang kamera sama tetapi kesan yang diperoleh berbeda. Sudut pandang kamera penting dalam menciptakan kesan-kesan tertentu,misalnya kesan horor.Kata kunci: iklan, semiotika, film, sinematografi